MIKROALGA SEBAGAI BIOINDIKATOR KUALITAS AIR PERMUKAAN Studi Awal : Hubungan Antara Konsentrasi Pigmen dan Berat Kering dalam Penentuan Kandungan Mikroalga Pada Sampel Air Artifisial - Rijal Hakiki (Journal of Environmental Engineering and Waste Management, 2016)
Abstract: Microalgae is the one of aquatic organism wich can be a bioindicators for surface water quality. Chlorophyll contain in a microalgae cell can be measured to know the abundance of microalga in a water body. Dry-weight biomass measurements is another method that can be used to know the abundance of microalga in a water body. both method have advantages and disadvantanges of each. In chlorophyll concentration measurements, the present of other compounds that can absorb light spectrum at measurements wavelength (Strickland and Parsons use 665 nm, 645 nm and 630 nm) result absorbance value higher than it should be. Turbidity level result by suspended particle content being a problem for dry-weight biomass measurements. Dry-weight biomass determination based on the approximation of chlorophyll content measurements was studied in this research.  The Results of simple regression analysis showed that there is a fairly strong positive correlation between chlorophyll content and dry-weight biomass (Ra = 0.870), which has the tendency to follow the linear regression equation y = 302,35x + 17,121. Dry-weight determination based on approximation of clorophyll content can be applied to the sample of water that has suspended particle content tend to be constant and inert (did not produce subtances that can react with organic solvent when chlorophyll extraction process occurred). Based on the processed datas, it can be conclude that the influence of another suspended particle content in a sample of water is not statistically significant.